Model Latihan Smash Bola Voli dengan Augmented Reality - Bayu Thomi Rizal; Junaidi Junaidi; Yusmawati Yusmawati; Widiastuti Widiastuti; Tito Parta Wibowo (Universitas Muhammadiyah Mataram, 2025)
Abstract: This research aims to produce a learning model and test the effectiveness of the learning model for basic volleyball smash techniques for high school students. The model developed in this study is focused on learning volleyball smash for high school students using an augmented reality approach. This research method uses the research and development (R&D) model of Borg and Gall. The research subjects were high school students with a total of 20 students for small trials, 40 students for large trials and an effectiveness test of 80 students consisting of 40 experimental group students and 40 control group students. The test instrument used is a volleyball smash basic technique learning test instrument that has been adapted to each stage of basic motion and has passed the validity test by several experts. The results showed that: (1) the learning model of basic volleyball smash techniques for high school students can be declared very feasible to be applied in learning physical education sports and health at school, (2) the effectiveness test of the volleyball smash basic technique learning model is empirically declared effective and significant in improving the basic technique of volleyball smash very well in high school students. The results of the N-gain test score of the experimental group obtained a Mean value = 63.30 or equal to 63.30% including in the moderately effective category. Meanwhile, the N-gain test results of the control group score obtained Mean = 47.55 or equal to 47.55% are included in the less effective category. So it can be concluded that the learning model for basic volleyball smash techniques with augmented reality is declared effective in improving the learning outcomes of basic volleyball smash techniques very well in high school students.Abstrak: Penelitian ini bertujuan untuk menghasilkan model pembelajaran dan menguji efektifitas model pembelajaran teknik dasar smash bola voli untuk siswa Sekolah Menengah Atas (SMA). Model yang dikembangkan dalam penelitian ini difokuskan pada pembelajaran smash bola voli untuk siswa SMA dengan menggunakan pendekatan augmented reality. Metode penelitian ini menggunakan research and development (R&D) model Borg and Gall. Subyek penelitian adalah siswa sekolah menengah atas dengan jumlah subyek 20 siswa untuk uji coba kecil, 40 siswa untuk uji coba besar dan uji efektifitas sebesar 80 siswa yang terdiri dari 40 siswa kelompok eksperimen dan 40 siswa kelompok kontrol. Instrumen test yang digunakan yaitu instrumen test pembelajaran teknik dasar smash bola voli yang telah disesuaikan dengan setiap tahapan gerak dasar dan telah melewati uji validitas oleh beberapa ahli. Hasil penelitian menunjukkan bahwa: (1) model pembelajaran teknik dasar smash bola voli untuk siswa SMA dapat dinyatakan sangat layak diterapkan dalam pembelajaran pendidikan jasmani olahraga dan kesehatan di sekolah, (2) uji efektifitas model pembelajaran teknik dasar smash bola voli dinyatakan secara empiris efektif dan signifikan dalam meningkatkan teknik dasar smash bola voli dengan sangat baik pada siswa SMA. Hasil uji N-gain Skor kelompok eksperimen diperoleh nilai Mean= 63,30 atau sama dengan 63,30% termasuk dalam kategori cukup efektif. Sedangkan, hasil uji N-gain Skor kelompok kontrol diperoleh nilai Mean= 47,55 atau sama dengan 47,55% termasuk dalam kategori kurang efektif. Maka dapat disimpulkan bahwa model pembelajaran teknik dasar smash bola voli dengan augmented reality dinyatakan efektif meningkatkan hasil belajar teknik dasar smash bola voli dengan sangat baik pada siswa SMA.